Rad54: The Master Key of All Machines in Homologous Recombination - Rashmi Holker; Parvendra Kumar Pal; Sandeep Kumar; Suman Verma (International Journal of Engineering and Management Research, 2021)
Homologous recombination (HR) is a type of genetic recombination required for DNA damage repair and error correction during chromosomal replication. This involves coordinated activities of proteins that belong to Rad52 epistasis group. Rad54, a Swi/Snf2 related protein of this group plays a crucial stimulatory role in homologous recombination repair. Rad54 connects early and late steps of homologous recombination through the network of interacting protein partners and a unique set of biochemical activities.